(untitled) (Academia Science Repository, 2023)
Improving the efficiency of the experimental teaching physics at a university requires accurate knowledge of the components and informative weight of knowledge. An example of the evaluation of the theoretical and experimental informativity of the content of the laboratory problem of the general physical workshop is given. A list of parameters has been developed, on the basis of which the corresponding scientific and methodological search is conducted. The research activity of a student is an indicator of the quality of education in a higher educational institution, which proves its relevance. In the context of an in-depth study of physics, it is this direction that becomes the most priority.